PERAN MEDIASI KEPUASAN PELANGGAN PADA PENGARUH E-SERVICE QUALITY, PERSEPSI HARGA, DAN PROMOSI PENJUALAN TERHADAP LOYALITAS PELANGGAN - Risa Septiani; Nurhadi Nurhadi (Universitas Ahmad Dahlan, 2020)
This study aim was to determine the effect of e-service quality, price perception, and sales promotion on customer loyalty through customer satisfaction on Gojek customers in Yogyakarta. This research is a quantitative study with survey method. The population in this study were Gojek customers in Yogyakarta. The sampling technique used was purposive sampling, with a total sample of 235 respondents. The technique of collecting data used an online questionnaire that has been tested for validity and reliability. The data analysis technique used to test the hypothesis was bootstrapping method using macro PROCESS by Andrew F. Hayes. The results of this study show that there is a positive effect of e-service quality on the satisfaction of Gojek Yogyakarta customers, there is a positive effect of price perception on the satisfaction of Gojek Yogyakarta customers, there is a positive effect of sales promotion on the satisfaction of Gojek Yogyakarta customers, there is a positive effect of customer satisfaction on the loyalty of Gojek Yogyakarta customers, there is a positive effect of e-service quality on the loyalty of Gojek Yogyakarta customers, there is a positive effect of price perception on the loyalty of Gojek Yogyakarta customers, there is a positive effect of sales promotion on the loyalty of Gojek Yogyakarta customers, and there is the effect of e service quality, price perception, and sales promotion on customer loyalty through Gojek Yogyakarta customer satisfaction, as evidenced by the e-service quality variable mediation coefficient of 0,0442; the mediation coefficient of price perception variable is 0,0404; and the mediation coefficient of sales promotion variable is 0.0676.